The third vaccine dose significantly reduces susceptibility to the B.1.1.529 (Omicron) SARS‐CoV‐2 variant. Issue 2 (17th January 2023) - Farias, Jéssica P.; Pinheiro, Josilene R.; Andreata‐Santos, Robert; Fogaça, Mayanna M. C.; da Silva Brito, Ruth D.; da Cruz, Edgar F.; de Castro‐Amarante, Maria F.; Pereira, Samuel S.; dos Santos Almeida, Shirley; Moreira, Ludimila M.; da Conceição Simões, Rafael; Luiz, Wilson B.; et al.
Abstract: The main coronavirus disease 2019 (COVID‐19) vaccine formulations used today are mainly based on the wild‐type severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike glycoprotein as an antigen. However, new virus variants capable of escaping neutralization activity of serum antibodies elicited in vaccinated individuals have emerged. The Omicron (B.1.1.529) variant caused epidemics in regions of the world in which most of the population has been vaccinated. In this study, we aimed to understand what determines individual's susceptibility to Omicron in a scenario of extensive vaccination. For that purpose, we collected nasopharynx swab ( n = 286) and blood samples ( n = 239) from flu‐like symptomatic patients, as well as their vaccination history against COVID‐19. We computed the data regarding vaccine history, COVID‐19 diagnosis, COVID‐19 serology, and viral genome sequencing to evaluate their impact on the number of infections. As main results, we showed that vaccination in general did not reduce the number of individuals infected by Omicron, even with an increased immune response found among vaccinated, noninfected individuals. Nonetheless, we found that individuals who received the third vaccine dose showed significantly reduced susceptibility to Omicron infections. A relevant evidence that support this finding was the higher virus neutralization capacity of serum samples of most patients who received the third vaccine dose. In summary, this study shows that boosting immune responses after a third vaccine dose reduces susceptibility to COVID‐19 caused by the Omicron variant. Results presented in this study are useful for future formulations of COVID‐19 vaccination policies.